2022
DOI: 10.1037/ort0000593
|View full text |Cite
|
Sign up to set email alerts
|

Latent class analysis of COVID-19 experiences, social distancing, and mental health.

Abstract: Information is needed on the relationship between coronavirus disease (COVID-19) social distancing restrictions and their relationship with mental health. In particular, there is limited investigation into how COVID-related adversities have positively mobilized individuals. We use latent class analysis (LCA) to identify subtypes of positive and negative aspects of the experience of COVID-19 social distancing and the association of these subtypes with mental health. We conduct an online survey of COVID-19 and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Despite the barriers to mental health produced by the pandemic, clients still need access to treatment. In fact, research demonstrates an increased need for mental health related interventions due to the stressors connected to the pandemic (Czeisler et al, 2020; Frounfelker et al, 2021; Runkle et al, 2021). Providers were not immune to the effects of COVID and it is possible that the LMHP population was impacted as severely, both physically and psychologically, as the general public.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Despite the barriers to mental health produced by the pandemic, clients still need access to treatment. In fact, research demonstrates an increased need for mental health related interventions due to the stressors connected to the pandemic (Czeisler et al, 2020; Frounfelker et al, 2021; Runkle et al, 2021). Providers were not immune to the effects of COVID and it is possible that the LMHP population was impacted as severely, both physically and psychologically, as the general public.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Governments worldwide adopted a range of drastic social restriction measures, such as city-wide lockdowns, cancelation of mass gathering events, travel bans, and a complete shutdown of the education system, all of which were aimed to curb COVID-19 transmission (Organisation for Economic Co-operation and Development, 2020). Alongside the proven effectiveness of such measures in decreasing the transmission of the virus (Ayouni et al, 2021), studies point to the negative effects and collateral damage of social restriction interventions on the general population’s mental health (see Frounfelker et al, 2022; Mahat-Shamir et al, 2023; Mahmud et al, 2022). Specifically, children and adolescents were particularly affected by the negative impacts of pandemic-related social distancing measures (Baumann, 2021; Romero et al, 2020; Sun et al, 2022).…”
Section: Psychological Effects Of Covid-19-related Social Distancing ...mentioning
confidence: 99%
“…6,20 For example, Frounfelker et al explored the typologies of positive and negative aspects of experiencing social distancing and identified 5 classes; they further reported that individuals in Hardships class were more likely to report a significant impact of COVID-19 on mental health than those in Low Impact class. 21 Likewise, Luk et al explored the multidimensional impact of COVID-related stressors and yielded 4 classes; compared to those in Minimal COVID-related Impact class, people in Serious Financial Stress class reported higher levels of perceived stress, anxiety, and depressive symptoms. 22 These studies suggest that individuals experiencing a more severe level of COVID-19 impacts are at higher risk for psychological distress than those who are less affected by the pandemic.…”
Section: Multidimensional Covid-19 Impacts and Mental Health Outcomesmentioning
confidence: 99%